2006
DOI: 10.1016/j.jaci.2005.12.1345
|View full text |Cite
|
Sign up to set email alerts
|

Cathelicidin deficiency predisposes to eczema herpeticum

Abstract: Background-The cathelicidin family of anti-microbial peptides is an integral component of the innate immune response that exhibits activity against bacterial, fungal and viral pathogens. Eczema herpeticum (ADEH) develops in a subset of AD patients due to disseminated infection with herpes simplex virus (HSV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
159
1
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(177 citation statements)
references
References 19 publications
7
159
1
10
Order By: Relevance
“…Understanding the mechanism by which IL-4 and IL-13 inhibit HBD expression is important because these cytokines are increased in AD skin and lavage fluid of CF patients (13,26). Additionally, the increased expression of IL-4 and IL-13 in AD skin is thought to increase the propensity of these patients to recurrent bacterial and viral skin infections by reducing AMP expression (5,16,27). In this study, we found that STAT-1 activation was inhibited by IL-4 and IL-13.…”
Section: Effect Of Socs-1 and Socs-3 Is Regulated By Stat-6mentioning
confidence: 99%
“…Understanding the mechanism by which IL-4 and IL-13 inhibit HBD expression is important because these cytokines are increased in AD skin and lavage fluid of CF patients (13,26). Additionally, the increased expression of IL-4 and IL-13 in AD skin is thought to increase the propensity of these patients to recurrent bacterial and viral skin infections by reducing AMP expression (5,16,27). In this study, we found that STAT-1 activation was inhibited by IL-4 and IL-13.…”
Section: Effect Of Socs-1 and Socs-3 Is Regulated By Stat-6mentioning
confidence: 99%
“…115 As mentioned earlier, cathelicidin exhibits antiviral activity against HSV and vaccinia virus, and cathelicidin expression is inversely correlated with serum IgE levels in EH patients. 116 Skin from atopic patients with eczema herpeticum show reduced expression of cathelicidin, and cathelicidin deficient mice show higher levels of HSV-2 replication. 116 Human and mouse cathelicidin reduce vaccinia virus plaque formation in vitro, and CRAMP knockout mice show more vaccinia pox formation than in control mice.…”
Section: Viral Infectionsmentioning
confidence: 99%
“…This finding suggests a role for SNP rs6509541 via Siglec-8 in allergic diseases because tIgE is a useful marker for assessing allergic diseases. 35 Given that Siglec-8 is a key molecule involved in facilitating eosinophil apoptosis and that mutations in Siglec-8 may also be involved in other allergic and eosinophilic disorders, we investigated whether Siglec-8 SNPs are associated with other human eosinophilic disorders like EE. We selected eight SNPs encompassing the Siglec-8 gene with a coverage of 2 kb/SNP, including those associated with asthma.…”
Section: Discussionmentioning
confidence: 99%